Pulmonary embolism and deep vein thrombosis: Similar but different. Issue 206 (October 2021) - Wenger, Nicolas; Sebastian, Tim; Engelberger, Rolf Peter; Kucher, Nils; Spirk, David
Abstract: Introduction: Pulmonary embolism (PE) and deep vein thrombosis (DVT), the two clinical manifestations of venous thromboembolism (VTE), constitute a major global burden of cardiovascular disease. They are often referred to as one disease but several patient characteristics, risk factors, real-world treatment, and clinical outcomes may differ substantially between PE and DVT alone. Materials and methods: We conducted a narrative review of the state-of-the-art literature on the topic of PE and DVT alone using PubMed, Google scholar, and MEDLINE databases and the most established international consensus statement guidelines for the management of VTE, focusing on the recommendations for diagnosis and treatment but also including epidemiological and clinical characteristics of VTE, highlighting similarities and differences between PE and DVT alone. Results: Several patient characteristics, risk factors, clinical manifestations, and outcomes differ substantially between PE versus DVT alone. Nevertheless, recommendations for both diagnosis and treatment are strikingly similar in the current guidelines for the management of DVT and PE, except for the indication for advanced reperfusion therapies. Conclusions: The differences in risk factors, clinical manifestations, and clinical outcomes between patients with PE versus DVT alone are only marginally addressed in the current consensus guidelines. More data is needed allowing proposal of evidence-based adjustments in the diagnostic and therapeutic strategies for these two manifestations of VTE. Tailored risk stratification and individualized management strategies for patients with PE and DVT alone may lead to a better prognosis, less recurrence and complications, and possibly to a gain of quality-adjusted life years in patients with VTE. Highlights: Pulmonary embolism and deep vein thrombosis are often referred to as one disease. Differences between PE and DVT are addressed marginally in the published guidelines. More research comparing diagnosis and treatment of PE and DVT alone is warranted. Imaging and interventional technique advances may foster personalized VTE management.